A four oxidative stress gene prognostic model and integrated immunity-analysis in pancreatic adenocarcinoma - Wang, Hao; Tian, Ruo-Fei; Liang, Xue; Fan, Jing; Duan, Zi-Chuan; Fan, Xin-Yu; Zhang, Jia-Jia; Yao, Dong-Sheng; Chen, Zhi-Nan; Li, Ling (Frontiers in Oncology, 2023)
Pancreatic adenocarcinoma (PAAD) is a highly aggressive gastrointestinal tumor characterized by a poor prognosis. Oxidative stress has great impacts on various pathophysiological activities of cells, especially on the occurrence and development of tumors. However, the relationship between oxidative stress related genes and PAAD patients’ prognosis remains unclear. In this study, we constructed a prognostic model for PAAD based on oxidative stress genes and evaluated its predictive value. By digging into a training set of The Cancer Genome Atlas (TCGA) database and three Gene Expression Omnibus (GEO) datasets, 55 differentially expressed oxidative stress genes were identified. Based on univariate Cox regression analysis, Kaplan-Meier analysis and multivariate Cox regression analysis, four genes including MET, FYN, CTTN and CDK1 significantly related to PAAD patient’s prognosis were selected and further applied for constructing a prognosis model, with a good accuracy verified by validation set and a nomogram established to predict patient’s survival for one or two years. Then, based on the risk score of the model, patients were divided into high and low risk groups with the median value of risk score as the cut-off value, and gene set enrichment analysis (GSEA) indicated that lots of immune related pathways, metabolic pathways and DNA repair pathways were significantly enriched in the high risk group as compared to that in the low risk group. Besides, the frequency of genetic mutations also varied widely between high and low risk groups. Moreover, immune infiltration analysis showed that the infiltration level of 23 immune cells as well as the expression of immune checkpoint related genes and synthetic driver genes of T cell proliferation significantly altered between high and low risk groups. Finally, the upregulation of these four genes’ protein and mRNA levels in PAAD have been verified by the clinical proteomic tumor analysis consortium (CPTAC) database and patients’ clinical tissue samples, respectively. In conclusion, we have successfully constructed a four oxidative stress gene prognostic model that has important predictive value for PAAD patients, and this model might be a promising guidance for prognostic prediction and efficacy monitoring in clinical individualized therapy.